Effect Green Human Resource Management on Green Innovation through Green Human Capital (Architecture Image Studies, 2025)
The current literature in the environmental management domain suggests that employee behavior is critical to improving environmental outcomes. Still, few studies have examined how human resource management (HRM) is linked to organisational green innovation. The study aims to investigate the relationship between green human resource management and green innovation in the manufacturing industry through the lens of green human capital. The study included 240 participants from various occupational levels, including frontline workers, entry-level management, middle management, and top management employees at various manufacturers in Semarang, Central Java, Indonesia. Data were gathered using stratified random sampling and analyzed using the partial least structural equation modeling (PLS-SEM) technique. As a result, GHRM made a positive contribution to organizational green innovation. The mediating effects of green human capital were also statistically significant. The study adds to the body of knowledge by investigating environmental protection using the human capital theory and providing empirical evidence on hypothesized relationships. Furthermore, the study broadens the GHRM scope by including predictors such as green human capital for improved manufacturing industry performance.